Non‐coding variation in disorders of sex development. Issue 2 (February 2017) - Baetens, D.; Mendonça, B.B.; Verdin, H.; Cools, M.; De Baere, E.
Abstract : Genetic studies in Disorders of Sex Development (DSD), representing a wide spectrum of developmental or functional conditions of the gonad, have mainly been oriented towards the coding genome. Application of genomic technologies, such as whole‐exome sequencing, result in a molecular genetic diagnosis in ∼50% of cases with DSD. Many of the genes mutated in DSD encode transcription factors such as SRY, SOX9, NR5A1, and FOXL2, characterized by a strictly regulated spatiotemporal expression. Hence, it can be hypothesized that at least part of the missing genetic variation in DSD can be explained by non‐coding mutations in regulatory elements that alter gene expression, either by reduced, mis‐ or overexpression of their target genes. In addition, structural variations such as translocations, deletions, duplications or inversions can affect the normal chromatin conformation by different mechanisms. Here, we review non‐coding defects in human DSD phenotypes and in animal models. The wide variety of non‐coding defects found in DSD emphasizes that the regulatory landscape of known and to be discovered DSD genes has to be taken into consideration when investigating the molecular pathogenesis of DSD. Abstract :